A hierarchical flood shelter location model for walking evacuation planning. (8th August 2021) - Lee, Yoon-Ha; Keum, Ho-Jun; Han, Kun-Yeun; Hong, Won-Hwa
ABSTRACT: Prior planning of shelters and evacuation routes is the foundation of effective and safe post flood management. In this study, a hierarchical model for emergency shelter location selection in preparation for immediate, short-term, and long-term floods was developed. To ensure the safety of evacuation routes, levels of walking evacuation risk were classified based on inundation depth and flow rate, and high-risk areas were set as barriers in the network analysis. Accessibility, safety from inundation, service accessibility, and facility capacity were set as criteria for location selection to ensure evacuation safety and the capacity to provide the services necessary to maintain the lives of evacuees in shelters. Candidate locations in a flood shelter case study area were selected, and their characteristics compared with those of existing designated shelters via a grading system. The candidate shelters were found to be preferable in terms of safety and service capacity. The model presented here considers the viability of walking evacuation on flooded roads and a selection of methodologies for each type of flood shelter, thereby providing insight into the design of an integrative model to address the complex decision-making processes involved in flood shelter selection and post-flood management.